Hybrid 1-D dielectric microcavity: Fabrication and spectroscopic assessment of glass-based sub-wavelength structures - Stefano Taccheo (Ceramics International, 2015)
Two different 1-D multilayer dielectric microcavities are presented, one activated by Er3+ ions fabricated by rf-sputtering and other one containing CdSe@Cd0.5Zn0.5S quantum dots obtained by a hybrid radio frequency-sputtering/solution deposition process. The rare-earth activated cavity is constituted by an Er3+ -doped SiO2 active layer inserted between two Bragg reflectors consisting of 10 pairs of SiO2/TiO2 layers. Starting from the deposition procedure used for this cavity a fabrication protocol was defined with the aim to combine the high reproducibility allowed by the sputtering deposition for the fabrication of multilayers structures with the ability of fabricate films activated with highly luminescent quantum dots dispersed in polymeric matrix. In this case the cavity was constituted by poly-laurylmethacrylate host matrix containing CdSe@Cd0.5Zn0.5S quantum dots inserted between two Bragg reflectors consisting of 10 pairs of SiO2/TiO2 layers fabricated by rf-sputtering on SiO2 substrate. The thicknesses of the films of the Bragg reflectors were tailored in order to reflect the visible radiation at around 650 nm. Transmittance spectra were employed to assess the optical features of the single Bragg gratings and whole samples. Luminescence measurements put in evidence that emissions strongly influenced by the presence of the cavities for both the samples.